An exact elasticity model for rib-stiffened plates covered by decoupling acoustic coating layers. (January 2015) - Xin, F.X.
Abstract: This paper presents an exact elasticity model for a fluid-loaded periodically rib-stiffened plate covered by a decoupling acoustic coating layer, which is built upon the plain strain elasticity theory. The acoustical coating layer is assumed to be perfectly bonded to the parallelly rib-stiffened plate, which is impinged by a time-harmonic plane sound wave. The theoretical model begins with Navier–Cauchy equations of motion to describe the vibration behavior of the rib-stiffened plate and the acoustic coating layer, and utilizes the acoustic equation to model the fluid motion. Applying the continuities of displacements and stresses at the interfaces of the plate, the coating layer and the fluid mediums, the vibroacoustic governing equation can be solved to obtain the sound transmission loss (STL) of the structure. The plane strain model is verified by comparing with the thin-plate model, and good agreements have been achieved between the two predictions. Based upon the theoretical model, the influences of the geometrical parameters of the structure, sound incidence angle, the dilatation and shear wave speeds in the acoustic coating layer on the STL of the structure are numerically explored. Results reveal the significant effect of the decoupling acoustic coating layer on the noise reduction of the periodically rib-stiffened structures.